(3MGTjI GdHNGQi Ydi JUQja GdYRis - (3fhQ GdOjf Ydj Hf Ydj GdHNGQjs; (3GddbGfj , fGUQ GdOjf CHh YHO Gddg,J (B958 (3g` s
(3ChdgG (B:s
(3CeG HYOagPg MhGTi Ydi ehGVY ef MGTjI SjOfG GddbGfi Ydi TQM JUQja GdYRi ddYdGeI GdJaJGRGfi s
(3BNQgG (B:s
(3ai HjGf GSJZQGb GdeaQO hGdLeY efcQG Ch eYQa aYdjg GfJgi s
(3MGTjI GddbGfi Ydi TQM JUQja GdYRi (B" (3NdGUI GdJYQja HObGFb TQM GdJUQja(B" (3GfXQ cTa GdXfhf L(B2 (3U` (B1139s
(3TQM JUQja GdYRi ddJaJGRGfis
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdUQas